Global Attractors for the Three-Dimensional Viscous Primitive Equations of Large-Scale Atmosphere in Log-Pressure Coordinate - Bo You; Shan Ma (Abstract and Applied Analysis)
We will first prove the existence of - and -absorbing sets for the three-dimensional primitive equations of large-scale atmosphere in log-pressure coordinate and then prove the existence of -absorbing set by the use of the elliptic regularity theory. Finally, we obtain the existence of - and -global attractors for the three-dimensional viscous primitive equations of large-scale atmosphere in log-pressure coordinate by using the Sobolev compactness embedding theory.